The Na⋅⋅⋅B Bond in NaBH3 - : A Different Type of Bond - Foroutan-Nejad, Cina (Angewandte Chemie (International ed. in English), 2020)
A newly introduced Na-B bond in NaBH3 - has been a challenge for the chemical bonding community. Here, a series of MBH3 - (M=Li, Na, K) species and NaB(CN)3 - are studied within the context of quantum chemical topology approaches. The analyses suggest that M-B interaction cannot be classified as an ordinary covalent, dative, or even simple ionic interaction. The interactions are controlled by coulombic forces between the metals and the substituents on boron, for example, H or CN, more than the direct M-B interaction. On the other hand, while the characteristics of the (3, -1) critical points of the bonds are comparable to weak hydrogen bonds, not covalent bonds, the metal and boron share a substantial sum of electrons. To the best of the author's knowledge, the characteristics of these bonds are unprecedented among known molecules. Considering all paradoxical properties of these bonds, they are herein described as ionic-enforced covalent bonds.
Keywords: covalent bonds; bond analysis; quantum chemistry; sodium; electrostatic interactions